2020
DOI: 10.21037/atm-20-6342
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor magnetic resonance imaging of white matter integrity in patients with HIV-associated neurocognitive disorders

Abstract: Background: This study investigated the efficacy and neurotoxicity of highly active antiretroviral therapy (HAART) by evaluating white matter (WM) injury using diffusion tensor magnetic resonance imaging (DTI) in patients with human immunodeficiency virus (HIV)-associated neurocognitive disorders (HAND).Methods: Forty-six patients with HAND underwent DTI before and every six months during HAART treatment. DTI data, including fractional anisotropy (FA) and mean diffusivity (MD) values of structural WM before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The virus in the cerebrospinal fluid could penetrate the cerebrospinal fluid brain barrier and directly or indirectly cause damage around the lateral ventricles, which is a possible explanation. White matter damage and disconnection from the cortex may occur in PLWH with milder cognitive impairment, and the pathological changes are likely to be the axonal chronic injury ( Li et al, 2018 ; Zhao et al, 2020 ) and may cause the atrophy of the gray matter, and then the bilateral lateral ventricles expand. Furthermore, in this research, the lower CD4 + /CD8 + ratio was associated with larger left lateral ventricle and ventricular system.…”
Section: Discussionmentioning
confidence: 99%
“…The virus in the cerebrospinal fluid could penetrate the cerebrospinal fluid brain barrier and directly or indirectly cause damage around the lateral ventricles, which is a possible explanation. White matter damage and disconnection from the cortex may occur in PLWH with milder cognitive impairment, and the pathological changes are likely to be the axonal chronic injury ( Li et al, 2018 ; Zhao et al, 2020 ) and may cause the atrophy of the gray matter, and then the bilateral lateral ventricles expand. Furthermore, in this research, the lower CD4 + /CD8 + ratio was associated with larger left lateral ventricle and ventricular system.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the statistical information in Table 2 , we grouped three studies ( 35 , 41 , 44 ) into older subgroups because their participants were older in several studies. We grouped the two studies ( 40 , 55 ) into the same subgroup because they were the only follow-up studies in the study. Since these three studies ( 39 , 43 , 57 ) were fully tested on the NP and cognitive scales, we assigned them to the same subgroup.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, using diffusion MRI data obtained from 30 adults with and 31 without HIV disease, we examined mean FA within the corpus callosum, forceps minor, and right uncinate fasciculus, regions commonly known to be affected by HIV disease 1,16,17 . Although the corpus callosum is the most reported region when examining WM differences in PWH, 18 multiple studies have found differences across multiple projection and association fiber tracts including the forceps minor and right uncinate fasciculus 19–21 . These regions were also selected because they differ in size (specifically, the corpus callosum is a large WM tract, the forceps minor is a medium size tract, and the right uncinate fasciculus is a small WM tract), and therefore might benefit differently from local and nonlocal PCA denoising approaches.…”
Section: Introductionmentioning
confidence: 99%
“…1,16,17 Although the corpus callosum is the most reported region when examining WM differences in PWH, 18 multiple studies have found differences across multiple projection and association fiber tracts including the forceps minor and right uncinate fasciculus. [19][20][21] These regions were also selected because they differ in size (specifically, the corpus callosum is a large WM tract, the forceps minor is a medium size tract, and the right uncinate fasciculus is a small WM tract), and therefore might benefit differently from local and nonlocal PCA denoising approaches. Specifically, larger WM tracts are expected to directly benefit from local PCA denoising, whereas smaller WM tracts that are susceptible to partial volume effect might benefit more from nonlocal PCA denoising.…”
Section: Introductionmentioning
confidence: 99%